A rare case report of pseudo-pregnancy in a menopausal female - Mini Sharma; Pavitra Shankar; Prerna Kukreti; Dinesh Kataria (Indian Journal of Psychiatry)
Pseudo-pregnancy is an uncommon psychiatric presentation, often having a complex interplay of psycho-social factors making it difficult to manage. It is common to present in the reproductive age range, rarely in postmenopausal women. We are reporting a rare presentation of a 48-year post-menopausal widowed HIV-positive female with no live issues having two years of secondary amenorrhea complaining to have documented weight gain and experience of perceiving fetal movements for the past 5 months. However, she persistently insisted on antenatal care despite repeated reports of ultra-sonographic pelvis imaging and gynecological examination pointed toward menopausal changes and the absence of any live issue. This case report emphasizes the clinical presentation and management strategies for patients with pseudocyesis, a peculiar and rare psychiatric manifestation.